IMPACT ASSESSMENT OF COMBINED HEAT AND POWER PLANTS (CHPPs) IN ALMATY: PM2.5 SIMULATIONS OVER THE CITY USING WRF-AERMOD MODELS WITH VERIFICATION USING GROUND LEVEL MEASUREMENTS - Ogbuabia, Theophilus Bright (School of Engineering and Digital Sciences, 2023)
Air pollution in Kazakhstan has been a major issue over the last few decades as the country’s industrial sector is experiencing a major boom. Kazakhstan’s largest and busiest city, Almaty, has been ranked by WHO among the most polluted cities in the world. One of the major air pollutants is PM2.5, with an average yearly concentration that is about six times higher than the WHO recommended value of 5μg/m3. Several attempts have been made by the government to curb the air pollution threat in the country, especially in its busiest city, including introducing buses for public transportation that are powered by solar and investing in solar energy and other green energy sources. However, these efforts have not yielded enough results. Hence, there is a need to investigate the various sources of PM2.5 so as to direct the preventive efforts of the government to the major sources of these pollutants, which will be more effective in curbing air pollution. One such source is the power plants in Almaty. One of the major sources of PM2.5 is the combined heat and power plants (CHPP) which is a system of co-generation of electricity and power. About 80% of power generation in Almaty is done by CHPP, which uses coal as its major source of fuel. In this study, the emissions of the major power plants in Almaty, CHPP-2 and CHPP-3, were used to perform a simulation using the US Environmental Protection Agency’s (EPA) approved air dispersion model (AERMOD) and the weather research and forecasting model (WRF). Necessitated by the unavailability of emission data from the power plants, two scenarios of the simulation were done: controlled and uncontrolled. In the controlled and uncontrolled scenarios, the emissions from the CHPPs were calculated using the controlled and uncontrolled emission factors from AP-142 table 1.1-7. The results showed that if the control mechanism in the CHPP functions at maximum efficiency, the impact of the CHPP emission on the total concentration of emission will be negligible, which is about 6% on average, while for an uncontrolled CHPP, the emission will be contributing about 30% on an average to the total PM2.5 concentration in Almaty.
Keywords: type of access: embargo; Air Pollution; Weather Research and Forecasting Model; Air Dispersion Model; PM2.5; Combined Heat and Power Plants (CHPP); Almaty; Kazakhstan